Pengaruh Penggunaan Teknologi Terhadap Sikap Toleransi Petani Dalam Menghadapi Risiko Usahatani Jagung Di Kecamatan Bandar Baru Kabupaten Pidie Jaya - Yulia Fadhilah; Fajri Jakfar; Indra Zainun (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
Corn is one of the food crops cultivated in Aceh Province, precisely in Bandar Baru District, Pidie Jaya Regency. Local corn farmers are soybean farmers who replace crop commodities for cultivation because the selling price of soybeans is lower than the price of corn. The existence of farming risk that occurs forces farmers to have a tolerance attitude towards risk so that the farming that is run will still exist even though the risk occurs. The purpose of this study was to find out what technology has been applied by corn farmers in Bandar Baru District and how the influence of technology use on farmers' tolerance in dealing with corn farming risks. The results of the study show that there have been many application technologies adopted by farmers in Bandar Baru District, 43% of them have reached the high category. The technology that has been applied by corn farmers in Bandar Baru District is the use of superior varieties, quality seeds, botanical pesticides, integrated pest control, tractors, weeding tools, corn shellers, pesticide sprayers, sanitation, rain-fed systems, and drying systems. Then corn farmers in Bandar Baru District who adopt high category application technology are more tolerant of corn farming risks.